2011
DOI: 10.1007/s10526-011-9343-0
|View full text |Cite
|
Sign up to set email alerts
|

Lethal and sublethal effects of Iranian isolates of Steinernema feltiae and Heterorhabditis bacteriophora on the Colorado potato beetle, Leptinotarsa decemlineata

Abstract: To determine the LC 50 values of two entomopathogenic nematodes against Leptinotarsa decemlineata Say (Coleoptera: Chrysomelidae) prepupae, different concentrations of the nematodes were tested in soil. Because of the different temperature requirements of the two nematode species, bioassay experiments were conducted at 20 ± 1°C and 27 ± 2°C for Steinernema feltiae Filipjev (Rhabditida: Steinernematidae) and Heterorhabditis bacteriophora Poinar (Rhabditida: Heterorhabditidae), respectively. Both the isolates we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…Cellular encapsulation of the EPNs has been reported in CPB (Armer et al, 2004;Ebrahimi, Niknam, & Dunphy, 2011;Ebrahimi, Niknam, & Lewis, 2011;Thurston et al, 1994) and, in part may decrease THC. Plasmatocytes and granulocytes are the main haemocytes involved in encapsulation response of the insects against EPNs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cellular encapsulation of the EPNs has been reported in CPB (Armer et al, 2004;Ebrahimi, Niknam, & Dunphy, 2011;Ebrahimi, Niknam, & Lewis, 2011;Thurston et al, 1994) and, in part may decrease THC. Plasmatocytes and granulocytes are the main haemocytes involved in encapsulation response of the insects against EPNs.…”
Section: Discussionmentioning
confidence: 99%
“…PO activation in nematode-injected CPB larvae is expected since cellular encapsulation and capsule melanisation are common responses of CPB against EPNs (Armer et al, 2004;Ebrahimi, Niknam, & Dunphy, 2011;Ebrahimi, Niknam, & Lewis, 2011;Thurston et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2000 Saffari, Madadi, and Karimi (2013) In another study, Ebrahimi, Niknam, and Lewis (2011) assessed the lethal and sub-lethal effects of two isolates of S. feltiae and H. bacteriophora against the prepupae of CPB in soil at two different temperatures. Their results revealed that both isolates were effective against L. decemlineata although H. bacteriophora was more effective at lower concentrations than S. feltiae.…”
Section: Entomopathogenic Nematodes Application Against Vegetable Andmentioning
confidence: 99%